Design and Implementation of an Arduino Based Smart Fingerprint Authentication System for Key Security Locker - Bong Siaw Wee (International ABEC, 2021)
Human beings have always prioritized security. Simple mechanical locks with the key as the authentication factor were among the earliest forms of security. A key is a tiny, shaped piece of metal with incisions made to match the wards of a certain lock that is placed into the lock and twisted to open or close it. People tend to misplace the keys and it is troublesome for other users to use the keys because it is hard to find the right key. Moreover, the keys are without any protection. Anyone besides the user can easily access the keys. Therefore, an Arduino Based Smart Fingerprint Authentication System for Key Security Locker was proposed and developed in this research. The Key Security Locker System is designed to make sure that the keys are stored in a more organized and effective location. Biometrics is the science of determining an individual's identification based on physical, chemical, or behavioral characteristics. The importance of biometrics in modern society has been strengthened by the necessity for large-scale identity management systems, the operation of which is dependent on the precise assessment of an individual's identity in the context of many applications. This technology recognizes authorized personal's unique fingerprints and allows them access. To utilize the fingerprint scanner, the user must place their finger on it. The event will capture new human minutiae through fingerprint scanning. These new minutiae will be compared to those in the database to determine if the individual is authorized or nonauthorized. The Liquid-Crystal Display (LCD) will show "Fingerprint Match" if the fingerprint matches the fingerprint in the database. Then, the microcontroller will instruct relay and solenoid lock to unlock the locker door. If the fingerprint is not matched, the LCD will appear "Not Matching". Then, the locker door will remain locked. Hence, the proposed system provides better security, higher efficiency, and in many instances, increased user convenience due to it being built based on a biometric system.